Health System Resilience: What Are We Talking About? A Scoping Review Mapping Characteristics and Keywords - Fridell, My (Int J Health Policy Manag, 2019)
Background: Health systems are based on 6 functions that need to work together at all times to effectively deliver safe and quality health services. These functions are vulnerable to shocks and changes; if a health system is unable to withstand the pressure from a shock, it may cease to function or collapse. The concept of resilience has been introduced with the goal of strengthening health systems to avoid disruption or collapse. The concept is new within health systems research, and no common description exists to describe its meaning. The aim of this study is to summarize and characterize the existing descriptions of health system resilience to improve understanding of the concept. Methods and Analysis: A scoping review was undertaken to identify the descriptions and characteristics of health system resilience. Four databases and gray literature were searched using the keywords "health system" and "resilience" for published documents that included descriptions, frameworks or characteristics of health system resilience. Additional documents were identified from reference lists. Four expert consultations were conducted to gain a broader perspective. Descriptions were analysed by studying the frequency of key terms and were characterized by using the World Health Organization (WHO) health system framework. The scoping review identified eleven sources with descriptions and 24 sources that presented characteristics of health system resilience. Frequently used terms that were identified in the literature were shock, adapt, maintain, absorb and respond. Change and learning were also identified when combining the findings from the descriptions, characteristics and expert consultations. Leadership and governance were recognized as the most important building block for creating health system resilience. Discussion: No single description of health system resilience was used consistently. A variation was observed on how resilience is described and to what depth it was explained in the existing literature. The descriptions of health system resilience primarily focus on major shocks. Adjustments to long-term changes and the element of learning should be considered for a better understating of health system resilience.